In vitro study on the inhibitory effect of various essential oils against murine coronavirus mouse hepatitis virus A-59 replication - Karelle Contant; Shiv Shankar; Monique Lacroix (Phytomedicine Plus)
Background: The spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) worldwide has become one of the biggest health problems due to the lack of knowledge about effective therapy. Purpose: Some scientific studies have shown that essential oils (EOs) have anti-inflammatory, immunomodulatory, and antiviral properties. Study design: This study demonstrated the potential antiviral activity of EOs in emulsion and in vapor forms to reduce the replication of MHV-A59, a murine surrogate of SARS-CoV-2. Methods: In the present study, 32 EOs were screened in vitro against MHV-A59 on DBT cells using plaque assay. EOs in emulsions were applied at their maximum noncytotoxic concentrations to MHV-A59 after penetration of the viruses into the host cells for 1 h during intracellular virus replication. Results: Monarda didyma at 5000 µg/ml showed a reduction of 100% of viral plaque. Tanacetum annuum at 10000 µg/ml inhibited 5.03-log MHV-A59. Beyond 4-log, the drug can be qualified as an antiviral according to the guidelines of ICH. In vapor form, none of the EOs showed potential inhibitory effects against MHV-A59. Conclusion: Results demonstrated that all 32 undiluted EOs, incubated with MHV-A59 for 30 min, had a ≤1.09-log inactivation compared to an untreated virus. The findings of this study may provide proof-of-concept and insight into related trials.